“We will give you recite, and you will not forget” (Quran, 87:6). A tale of the Kazan Khan and his clever vizier - Zaytsev I.V. (Золотоордынское обозрение)
Purpose of the study: To analyze the text and present a translation of the latifeh anecdote about the clever vizier of the Kazan Khan. Research materials: The archive of Rizaetdin Fakhretdin. Results and scientific novelty of the study: the study is based on the publication and translation of the text, an anecdote – latifeh – about the clever vizier of the Kazan Khan who escaped death with the help of a cunning reading of an unvoiced Persian text in Arabic. The latifeh has been preserved in the archive and with a high degree of probability belongs to the pen of a very prolific poet and highly educated representative of the Muslim clergy of the Volga-Ural region, ‘Ali Chokry ((1827/28–1889). The list presented for research is currently stored in the Institute of Oriental Manuscripts of the Russian Academy Sciences in St. Petersburg. It is in its composition that the published anecdote is stored. This anecdote about “Sonkor-bik Kalanis” is also of Persian origin, since it arose in a Turkic environment where Farsi was well known. Perhaps it refers to the era of the Kazan Khanate, but we have no information about the existence in that state of the position of vizier under the khan. However, as an example of playing on words of an anecdotal nature, this story could well have appeared in the Volga region in the early Middle Ages. After all, it is based on the difference in reading the Arabic language and Turkic speech recorded in Arabic script. The Turks and Arabs faced this problem as soon as Islam penetrated the Turkic environment and their acquaintance with the Koran began. Thus, the “Latifeh about the Kazan Khan and his Vizier” is not just an interesting and funny anecdote, but an instructive philological puzzle that came to the mind of a sophisticated connoisseur of the three major languages of Islam – Arabic, Farsi, and Turkic.